2018
DOI: 10.3389/fphar.2018.00361
|View full text |Cite|
|
Sign up to set email alerts
|

Mequindox Induced Genotoxicity and Carcinogenicity in Mice

Abstract: Mequindox (MEQ), acting as an inhibitor of deoxyribonucleic acid (DNA) synthesis, is a synthetic heterocyclic N-oxides. To investigate the potential carcinogenicity of MEQ, four groups of Kun-Ming (KM) mice (50 mice/sex/group) were fed with diets containing MEQ (0, 25, 55, and 110 mg/kg) for one and a half years. The result showed adverse effects on body weights, feed consumption, hematology, serum chemistry, organ weights, relative organ weights, and incidence of tumors during most of the study period. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Together with genotoxic findings of MEQ, two primary metabolites of MEQ were concluded to be genotoxic in a battery of four different short-term tests, including mouse lymphoma assay (MLA), Ames test, chromosomal aberration assay and bone marrow erythrocyte micronucleus assay ( Liu et al, 2016 , 2017d ). A recent study suggested that MEQ induced genotoxicity and carcinogenicity in mice ( Liu et al, 2018b ). However, despite many years of usage in food producing animals, the toxic characteristics of MEQ, including its major toxic effects on the reproduction and development, had not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Together with genotoxic findings of MEQ, two primary metabolites of MEQ were concluded to be genotoxic in a battery of four different short-term tests, including mouse lymphoma assay (MLA), Ames test, chromosomal aberration assay and bone marrow erythrocyte micronucleus assay ( Liu et al, 2016 , 2017d ). A recent study suggested that MEQ induced genotoxicity and carcinogenicity in mice ( Liu et al, 2018b ). However, despite many years of usage in food producing animals, the toxic characteristics of MEQ, including its major toxic effects on the reproduction and development, had not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that Qx can cause toxic side effects such as trichothecation, photosensitivity, and adrenal cortical damage in livestock and poultry. More seriously, drug residues in animal-derived foods can pose a significant threat to the population directly consuming them [ 4 , 5 , 6 ]. According to the latest reports, the quinoxalines desoxymetabolites (desoxyquinoxalines, DQx) have the highest residues and have been identified as major toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high antimicrobial activity, QdNOs have recently been applied in the aquaculture industry . However, QdNOs can induce severe toxic effects, including cytotoxicity, photoallergy, mutagenicity, and carcinogenicity . Consequently, close attention should be paid to exposure of QdNOs and the metabolites in diet.…”
Section: Introductionmentioning
confidence: 99%